Patterns and representation in play-based learning: a systematic meta-synthesis of empirical studies in K-13+ settings - Dean, Steph N.; Wenner, Julianne A. (Frontiers in Education, 2025)
This systematic review provides a comprehensive meta-synthesis that examines empirical research on the implementation of play-based learning in formal educational settings. The review aims to identify patterns in the enactment of play-based learning, including its representation across academic disciplines, methodologies, grade levels, geographic contexts, and key indicators of play—choice, wonder, and delight. A comprehensive search across nine databases yielded 1,475 studies, of which 87 met stringent inclusion criteria: empirical, K-13+ formal settings, and an intentional learning objective tied to play. We extracted data from each study and used thematic synthesis to analyze patterns across multiple dimensions. Findings indicate that play-based learning is predominantly explored in early childhood and elementary education, with limited research on its implementation in secondary and post-secondary contexts. Studies were concentrated in North America and Europe, highlighting a need for greater geographic diversity. Findings also reveal significant gaps in nature-based play and its role in formal learning environments. Limitations include potential selection bias due to English-language restrictions and the exclusion of studies without a curricular focus. This review underscores the need for broader research on play-based learning, particularly in underrepresented populations and adolescent education. By providing a systematic overview of current research trends and limitations, this meta-synthesis contributes to the growing body of knowledge on play-based learning and informs future research directions.